Coping-Style Behavior Identified by a Survey of Parent-of-Origin Effects in the Rat. Issue 10 (1st October 2018) - Mont, Carme; Hernandez-Pliego, Polinka; Cañete, Toni; Oliveras, Ignasi; Río-Álamos, Cristóbal; Blázquez, Gloria; López-Aumatell, Regina; Martínez-Membrives, Esther; Tobeña, Adolf; Flint, Jonathan; Fernández-Teruel, Alberto; Mott, Richard
Abstract: In this study we investigate the effects of parent of origin on complex traits in the laboratory rat, with a focus on coping style behavior in stressful situations. We develop theory, based on earlier work, to partition heritability into a component due to a combination of parent of origin, maternal, paternal and shared environment, and another component that estimates classical additive genetic variance. We use this theory to investigate the effects on heritability of the parental origin of alleles in 798 outbred heterogeneous stock rats across 199 complex traits. Parent-of-origin-like heritability was on average 2.7fold larger than classical additive heritability. Among the phenotypes with the most enhanced parent-of-origin heritability were 10 coping style behaviors, with average 3.2 fold heritability enrichment. To confirm these findings on coping behavior, and to eliminate the possibility that the parent of origin effects are due to confounding with shared environment, we performed a reciprocal F1 cross between the behaviorally divergent RHA and RLA rat strains. We observed parent-of-origin effects on F1 rat anxiety/coping-related behavior in the Elevated Zero Maze test. Our study is the first to assess genetic parent-of-origin effects in rats, and confirm earlier findings in mice that such effects influence coping and impulsive behavior, and suggest these effects might be significant in other mammals, including humans.